The Effect of E-Service Quality on Satisfaction and Its Impact on Customer Loyalty of Mobile Banking Users (Case Study of Bank Syariah Mandiri KCP Belawan) - Marliyah, Marliyah; Ridwan, M.; Sari, Ayu Kartika (Budapest International Research and Critics University, 2021)
Bank Syariah Mandiri (BSM) is a real example of a bank that has utilized information technology as an additional service provided to improve the customer experience in transacting online via the internet, namely through a mobile banking application. The application of mobile banking is one form of BSM's commitment in providing good quality electronic services, and can be felt and assessed by customers who have used it. These assessments can then affect their level of satisfaction. Based on this, it then encouraged researchers to test the influence of the quality of mobile banking electronic services offered by Bank Syariah Mandiri KCP Belawan on the satisfaction and loyalty of mobile banking users. This research is intended to analyze the effect of e-service quality on customer satisfaction and its impact on customer loyalty. Questionnaire items used as many as 35 items. Data collection is done by distributing questionnaires to customers of Bank Syariah Mandiri KCP Belawan who at least have an account and use BSM mobile banking application for 3 (three) months with a sample number of 84 people determined by nonprobability sampling method. The analytical technique used is Structural Equation Modeling Partial Least Square (SEM-PLS). The results obtained in this study are that: (1) The relationship of e-service quality has a positive and significant effect on customer satisfaction. This can be proven from the t-value greater than 1.96 which is 13,230. Thus, H1 in this study was accepted. (2) The relationship of e-service quality has a positive and significant effect on customer loyalty. This can be proven from the t-value greater than 1.96 which is 3,267. Thus, H2 in this study was accepted. (3) Customer satisfaction relationship has a positive and significant effect on customer loyalty. This can be proven from the t-value greater than 1.96 which is 3,666. Thus, H3 in this study was accepted.